Autoregressive Models Used for Forecasting the Prices of Animals for Slaughter in Poland - Tłuczak, Agnieszka (Modele autoregresyjne w prognozowaniu cen żywca w Polsce, 2011)
The forecast of agricultural prices is one of the most important factors in making decision on production farms. The appropriate forecast allows for limiting the risk connected with one's economic activity. In this study autoregressive models have been used, which helped to determine the price forecast for agricultural products in the purchasing centres in the three quarters of 2010. To determine the quality of forecast the average ex-post errors of the past forecasts have been used. The achieved results show that autoregressive models are an effective tool in forecasting the agricultural prices in Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 113-124
Keywords: prognozowanie; produkty rolne; rynek żywca; prognozowanie cen; forecasting; agricultural products; livestock market; prediction of prices